Diseño arquitectónico de unidad educativa de básica y media para jornada única en la comuna de Cazucá en el municipio de Soacha. (2020)
The present work of investigation consists of the description and analysis of the current conditions of the schools of the commune of Cazucá in the municipality of Soacha. The problem on the other hand, arises from the concern to improve the current conditions of coverage of students in the commune. The informal growth without planning of public space or equipment, given by the displacement and the economic necessities, makes that the people who reside in the sector do not have access to quality education and there are problems of violence, delinquency and drug addiction. The research was carried out based on the study methodology developed in 5 stages, approaching the place, gathering information, diagnosis and analysis of the place, theoretical foundation and proposal. This helped for the proposal of the school of basic education and half a single day through sustainable architecture, and other criteria obtained according to the methodology used.